Peran Sistem Informasi Akuntansi Dalam Mencegah Kecurangan: Pendekatan Studi Di Tasikmalaya - Ridwan, Rizky; Lestari, Dheri Febiyani; Arifah, Alfin Nur; Abdurachman, Aditia (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
This study aims to investigate the relationship between Internal Governance and Accounting Information Systems with Fraud Prevention in the banking sector in Tasikmalaya. The population focused on employees of Bank BJB Syariah and Bank BSI. The sampling method used was Saturated Sampling. Data analysis was conducted through multiple linear regression using SPSS 16 software. The results showed that partially, there was no significant influence between the Accounting Information Systems and Fraud Prevention, as well as between Internal Governance and Fraud Prevention. Simultaneously, both also did not significantly affect Fraud Prevention. These findings provide important insights into the context of risk management and internal control in the banking industry, especially in Tasikmalaya. The implications can assist companies in designing more effective control strategies to reduce the risk of fraud and improve operational integrity. Keywords: Accounting Information Systems, Internal Governance, Fraud Prevention